2004
DOI: 10.1177/0310057x0403200419
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis with Associated Fibrinolysis, Reversed with Tranexamic Acid and Demonstrated by Thrombelastography

Abstract: In the surgical setting, fibrinolysis can be a serious complication of anaphylaxis. We present four cases of anaphylaxis that were associated with fibrinolysis during anaesthesia, and the use of the thrombelastograph to demonstrate this haemostatic defect and its correction using tranexamic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…We identified seven additional articles on hyperfibrinolysis diagnosed by thromboelastography. Oozing from the wound surface was observed in one patient reported by De Souza et al [18], whereas no bleeding complications were found in the other reports. Although four patients in whom the hyperfibrinolysis occurred during surgery were administered tranexamic acid and fresh frozen plasma intraoperatively, hyperfibrinolysis of the other three patients was resolved spontaneously within a few hours.…”
Section: Discussionmentioning
confidence: 73%
“…We identified seven additional articles on hyperfibrinolysis diagnosed by thromboelastography. Oozing from the wound surface was observed in one patient reported by De Souza et al [18], whereas no bleeding complications were found in the other reports. Although four patients in whom the hyperfibrinolysis occurred during surgery were administered tranexamic acid and fresh frozen plasma intraoperatively, hyperfibrinolysis of the other three patients was resolved spontaneously within a few hours.…”
Section: Discussionmentioning
confidence: 73%
“…Koami et al [4] described a case of oxaliplatin-induced anaphylaxis associated with hyperfibrinolysis demonstrated by ROTEM TM (rotational thromboelastometry) with spontaneous resolution and no bleeding sequelae. De Souza et al [5] reported a series of four cases of anaphylaxis-induced hyperfibrinolysis demonstrated by thromboelastography (TEG). They were all treated with tranexamic acid and one was also treated with fresh frozen plasma after which the TEG returned to normal.…”
Section: Discussionmentioning
confidence: 99%
“…However, if the surgery is emergent and must be continued, any hemodynamic instability should be managed judiciously. Fibrinolysis during anaphylaxis has been reported and should be kept in mind as it could increase the risk of perioperative bleeding [14]. …”
Section: Discussionmentioning
confidence: 99%